SIMULATION OF THE GEOTHERMAL RESERVOIR OF THERMA - NIGRITA, CENTRAL MACEDONIA, GREECE - Kavouri, K.; Arvanitis, A.; Athanassoulis, C.; Xenakis, M. (Bulletin of the Geological Society of Greece, 2016)
The geothermal field of Therma - Nigrita is among the most important low enthalpy fields in Greece. It is located at the SW part of the Strymon basin (Central Macedonia). The geothermal research at Nigrita was launched by IGME during 1980- 1982. Actually, it is exploited mainly for agricultural use and thermal spa. The geothermal field of Therma - Nigrita, officially characterized by Ministerial Decision, covers an area of 10 km², has a pressurized reservoir at 70-500 m depth, showing temperatures of 40-64°C and geothermal fluids containing large amounts of CO2. In this paper the development of a 3D model for the reservoir of Therma - Nigrita, is presented. For this purpose the FEFLOW code is employed which simulates fluid flow and heat transfer in the geothermal reservoir under transient state conditions. Following, three different management scenarios are tested for a ten-year period. The first scenario examines the evolution of the reservoir under no-exploitation conditions, the second one represents the current exploitation scheme and in the third scenario the production rates are doubled. According to the simulation results, the decrease in temperature is not expected greater than 1% for all scenarios, while the effect on hydraulic heads is significant for both scenarios 2 and 3.